Analisis Penerapan Prinsip 5C Pada Pembiayaan Multiguna dengan Akad Murabahah Di PT. Bank Sumut Kantor Cabang Pembantu Syariah Marelan Raya - Astri Astri; Ahmad Perdana Indra (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This research discusses the implementation of the 5C principles (compliance, character, capacity, capital, guarantee) in multipurpose financing using murabahah contracts. This research aims to evaluate the extent to which these aspects are integrated in sharia financing practices, with a focus on transparency, fairness and sustainability. It is hoped that the results of the analysis will provide insight into the effectiveness of implementing the 5C principles in the context of multipurpose murabahah financing. The method used in this research is a qualitative method. In a qualitative approach, this research utilizes in-depth interviews with stakeholders related to multipurpose financing based on murabahah contracts. Direct observations of the process of implementing the 5C principles were also carried out. Content analysis was used to extract qualitative findings, enabling an in-depth understanding of how the 5C principles are reflected in these financing practices. This approach opens up space for deeper interpretation and context.